Crust no one - Archer, Winnie (Archer, Winnie. Bread shop mystery., 2017)
Business is booming at Yeast of Eden. But with a deadly mystery taking over the seaside town of Santa Sofia, the Mexican bread shop can't possibly leaven a killer's appetite . . . For once, Ivy Culpepper feels fulfilled. An apprenticeship at Yeast of Eden has opened her world to time-honored baking techniques under owner Olaya Solis's guidance--as well as the freshest small-town gossip, courtesy of chatty regulars known as the Blackbird Ladies. Ivy even begins accepting that she and restaurateur Miguel Baptista may never again rekindle their romance--despite the undeniable tension between them . . . But she's tied to Miguel again when his trusted produce supplier goes missing. Old Hank Riviera's financial troubles would make anyone consider running away forever. And with his relationship woes, there are plenty of people who might want to see Hank disappear. As Ivy, with the help of her octogenarian sidekick, turns to the loose-lipped Blackbird Ladies for leads, she soon finds herself caught in a web of lies stickier than a batch of Olaya's popular pastries . . .